F169. Muscle evoked potentials after electrical stimulation to the spinal cord can monitor the cortico spinal tract. (May 2018) - Ando, Muneharu; Tamaki, Tetsuya
Abstract : Introduction: Muscle evoked potentials after electrical stimulation to the spinal cord [Sp(E)-MsEP] are stable and likely to be used for intraoperative spinal cord monitoring. However there is an opinion that Sp(E)-MsEP is not specific for being transferred via the cortico-spinal tract but can also be elicited by stimulation of the dorsal column alone. The aim of this study is to clarify that the spinal motor tract can be monitored by Sp(E)-MsEP. Methods: Five consecutive patients (4 women and 1 men), with an average age of 63.4 years (range, 40–74 years), were studied during the surgery of cervical or thoracic spine. We recorded MsEP by three types of stimulation methods (1. transcranial electrical stimulation to the brain, 2.electrical stimulation to the spinal cord, 3. simultaneous stimulation to the brain and spinal cord). 1. transcranial electrical stimulation to the brain: Cork screw type electrodes were inserted symmetrically into the outer table of the skull 5 cm lateral and 2 cm anterior to Cz (International 10–20 system). We used a 5 train stimulation of 2 ms ISI with 0.5 ms duration and 150–200 mA intensity. 2. electrical stimulation to the spinal cord: To stimulate the spinal cord, a catheter electrode was inserted into the epidural space caudal to the level of the lesion. Electrical stimulation was delivered as a 5 train stimulation of 2 ms ISI with 0.2 ms duration and 10–40 mA intensity. Results: In all patients at simultaneous stimulation to the brain and spinal cord, the wave form of MsEP from abductor hallucis muscle (AH) was similar of that by spinal cord stimulation. By collision method (simultaneous stimulation of Stim 1 and Stim 2), the wave form of the muscle evoked potential from AH muscle is same of that by not stim 1 but stim 2. It means that the volleys of cortico spinal tract after brain stimulation was collided by the antidromic volley after the stimulation to the spinal cord. In other words, electrical spinal cord stimulation can elicit the volleys travelling through the motor tracts. Conclusion: This collision study means that the volleys of cortico spinal tract after brain stimulation was collided by the antidromic volleys after spinal cord stimulation. Therefore we can monitor the motor tracts of the spinal cord using Sp(E)-MsEP.